Linguistic features of advertisements on road safety equipment in english - Nguyễn Thị Hồng Minh; Nguyễn Thị Quỳnh Hoa (ĐHĐN : ĐHĐN., 2015)
This thesis mainly aims at examining linguistic features of advertisements on road safety equipment (ARSEs) in English. The data of the study are 112 samples of ARSEs collected from prestigious websites in the United States and the United Kingdom. The data are described and analyzed on linguistic features under qualitative and quantitative approaches. On a close analysis, the thesis attempts to figure out some commonly used linguistic features of advertisements on road safety equipment in English in terms of syntactic features, lexical choices and cohesive devices in the views of Quirk, R. et al. and Halliday, M.A.K. and Hasan, R. in their books entitled “A Comprehensive Grammar of The English Language” and “Cohesion in English” respectively. The findings of this study show that the passive voice, relative clauses, conditional sentences, and imperative sentences are popularly used in advertisements on road safety equipment for the purpose of arousing the customers’ attention. Moreover, the use of weasel words, evaluative adjectives and verbs denoting commitment make the advertisements more appealing and persuasive. Besides, the use of grammatical and lexical cohesive devices makes the advertising language sound warm and friendly. It is hoped that the result of this study will really provide some practical applications for teaching and learning English. This study may also be useful for those who are interested in advertising, especially advertisements on road safety equipment.
Keywords: advertisements on road safety equipment in english; Linguistic features -- road safety equipment in english